2022
DOI: 10.1177/20662203211056486
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the working alliance: A qualitative study from the perspective of both probationers and probation officers

Abstract: The probationer–probation officer working alliance plays an important role in the outcome of probation supervision. This study explored the development of the working alliance between probationers and probation officers in the Netherlands, from the perspective of both probationers and probation officers. More specifically, we explored the significance of different aspects of the working alliance at the start of probation supervision and after a three-month period, as well as the role played by critical inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…2003; Sturm et al, 2022). The goals of the working alliance to promote engagement and receptivity to supervision standards align well with the principles of risk, needs, and responsivity (Andrews & Dowden, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2003; Sturm et al, 2022). The goals of the working alliance to promote engagement and receptivity to supervision standards align well with the principles of risk, needs, and responsivity (Andrews & Dowden, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Research overwhelmingly suggests that the working alliance between therapists and therapy clients is a robust and predictive factor for therapeutic outcomes (Horvath, 2001; Horvath & Greenberg, 1989; Horvath & Luborsky, 1993; Horvath & Symonds, 1991; Lambert, 1992; Lambert & Barley, 2001; Martin et al, 2000; Norcross & Lambert, 2006; Orlinsky et al, 2004). Researchers have further shown that the working alliance is also a robust factor impacting treatment completion and attrition rates (Blasko et al, 2018; Blasko & Jeglic, 2016; DeSorcy et al, 2016; Kozar & Day, 2012; Ross et al, 2008; Serran et al, 2003; Sturm et al, 2022). The goals of the working alliance to promote engagement and receptivity to supervision standards align well with the principles of risk, needs, and responsivity (Andrews & Dowden, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The working alliance is defined as the degree to which the therapeutic relationship is grounded in collaborative work with a shared purpose [28,29]. Whilst there exists a plethora of research into the alliance within voluntary therapy contexts, less is known about this alliance within forensic settings [30]. Dominant models of rehabilitation of those in custody emphasise the importance of the working alliance [31].…”
Section: The Relational Modelmentioning
confidence: 99%
“…More recently, there is growing interest in applying the concept of the working alliance to the fields of education (Estrada 2016) and social work (Horvath 2018), as well as executive and workplace coaching (Baron, Morin, and Morin 2011; De Haan et al 2016; Graßmann, Schölmerich, and Schermuly 2020; Kruger and Terblanche 2022). In addition, the concept has been applied to research on the professional–client relationship for attorneys (Tatman and Love 2010; McNamara 2012; McDonald, Morgan, and Metze 2016), probation officers (Sturm et al 2021, 2022), and other professionals within the criminal justice system.…”
Section: Introductionmentioning
confidence: 99%